Multidirectional action verbs of the russian language - E S Polyakova (Pashkina) (Russian Language Studies, 2013)
This paper is devoted to the analysis of the semantics of Russian multidirectional verbs of motion (type ходить ). The author casts doubt on the traditional for Russistics, Russian as a foreign language teaching and lexicography conception of unidirectional verbs (type идти ) being the peak of the lexical-semantic pair and the possibility of explaining the meaning of the multidirectional verb through the meaning of the unidirectional one. The paper considers such rarely discussed meanings of multidirectional verbs as ‘specific process’ and potential meaning, which leads to interesting results and refutes some conventional ideas of the so called “pair” (or twinned) verbs of motion of the Russian language.